Metabotropic glutamate receptor analogues inhibit p[NH]ppG-stimulated phospholipase C activity in bovine brain coated vesicles: involvement of a pertussis toxin-sensitive G-protein. - Martín, M (1995)
Guanosine 5'-[beta gamma-imido]triphosphate (p[NH]ppG)-stimulated phospholipase C (PLC) activity in bovine brain coated vesicles is inhibited by glutamate agonists. In the present study we show that quisqualic acid (QA), (+/-)-trans-1-aminocyclopentane-1,3-dicarboxylate (trans-ACPD), glutamic acid and ibotenic acid inhibited p[NH]ppG-stimulated PLC by 44, 41, 36 and 25% respectively. Carbachol also produced an inhibition of p[NH]ppG-stimulated PLC by 45%. The inhibition caused by trans-ACPD and QA was dose-dependent. DL-2-Amino-3-phosphonopropionic acid and (RS)-alpha-methyl-4-carboxyphenylglycine, specific antagonists of metabotropic glutamate receptors (mGluRs), abolished these inhibitory effects. trans-ACPD inhibition of p[NH]ppG-stimulated PLC was also observed in the presence of ionotropic glutamate receptor antagonists. When carbachol and QA or trans-ACPD were combined, additive inhibitory effects were observed. Preincubation of bovine brain coated vesicles with pertussis toxin abolished the inhibitory effects of mGluR analogues and carbachol on p[NH]ppG-stimulated PLC activity. The presence of Gs alpha and pertussis toxin substrates, Gi alpha and Go alpha subunits as well as PLC beta 1 in bovine brain coated vesicles has been confirmed by immunoblot. These results support the coupling of mGluRs to a PLC in an inhibitory manner through a pertussis toxin-sensitive G-protein in bovine brain coated vesicles.